Leaving "Hotel California": How Incentives Affect Flows of Benefits in the Netherlands - Jan C. van Ours (Vierteljahrshefte zur Wirtschaftsforschung, 2006)
This paper discusses developments in the Netherlands concerning unemployment insurance, unemployment assistance and disability insurance. The emphasis is on how financial incentives for individual workers and firms affect flows of benefit recipients. The main message is that it is indeed helpful to screen workers who want to enter the benefit system, to establish counseling and monitoring of workers that are in the benefit system and to impose sanctions on workers or employers that abuse the system. The Dutch experience in reconstructing social security provides clear lessons for other countries. – – Dieser Beitrag untersucht die Entwicklungen und Reformen der Arbeitslosenversicherung sowie der Renten- bzw. Erwerbsunfähigkeitsversicherung in den Niederlanden. Betrachtet wird vor allem, wie die damit verbundenen Anreize für Arbeitnehmer und Arbeitgeber die Ein- und Austritte in die Versicherungssysteme beeinflussen. Das wesentliche Ergebnis ist, dass es hilfreich ist, die Leistungsbezieher beim Eintritt zu untersuchen, vorhandene Leistungsbezieher laufend zu beraten und zu überprüfen und Missbrauch zu sanktionieren. Insoweit sind die niederländischen Erfahrungen für andere Länder hilfreich.
Keywords: 330; Arbeitslosenversicherung; Erwerbsminderungsrente; Arbeitsmarktpolitik; Reform; Niederlande